Pengalaman Pelanggan terhadap Minat Berkunjung Kembali pada Glamping Forest Garden Batulayang - Lioe Lyly Soemarni; Andine Sentana Wiradinata; Asep Parantika (Jurnal Manajemen Dirgantara, 2024)
This research intends to examine how much influence the effect customer experience revisit intention at Forest Garden Batulayang glaGlamping that it can help investors, manufacturers, and owners of glamping to understand and develop glamping’s quality through customers' experiences, which hopes to increase revisit intention so it can help glamping tourism development. This research uses a quantitative method. Data was collected using a questionnaire with a Likert scale, which was distributed by purposive sampling on a non-probability sampling technique with sample criteria that had used glamping services at Forest Garden Batulayang. Data were processed by SPSS version 22 for Windows and tested for data validity, reliability, and normality. Data was also analyzed using the hypothesis test and simple linear regression. The result of this research explains that there was an impact on customers' experiences that significantly influence revisit intention at Forest Garden Batutayang glamping by 67,9% from 92 samples analyzed from the 1109 population.